Clinical research and the law - Tereskerz, Patricia M. (Hoboken : John Wiley & Sons, 2012)
This book provides a comprehensive resource for medical professionals on the various legal aspects involved in conducting clinical research. It encompasses legal and ethical issues such as duty of care, research malpractice and negligence, standards of care, informed consent, liability issues for Institutional Review Boards (IRB), conflicts of interest, insider trading and the disclosure and withholding of clinical trial results. It will also provide legal guidance on research contracts, setting up clinical trials and common legal pitfalls encountered in medical research.
9.6 Health-care fraud.
Includes bibliographical references and index.
Print version record.
Keywords: Clinical medicine -- Research; Clinical trials -- Law and legislation; Biomedical Research -- legislation & jurisprudence -- United States; Biomedical Research -- legislation & jurisprudence; Biomedical Research -- standards -- United States; Clinical Trials as Topic -- legislation & jurisprudence -- United States; Clinical Trials as Topic -- standards -- United States; Medicine; Law; LAW -- Health; Clinical medicine -- Research; Clinical trials -- Law and legislation; Electronic books